BONTHUYS, BM Inventory of documents - BONTHUYS, BM (ARCA, 2017)
Speeches, programmes, memorial pieces and newspaper cuttings on election results
COVERAGE 1943-1981; 0,80 metres
Keywords: BONTHUYS, BM; Inventories; Politicians; National Party